(untitled) (Bangladesh Journal of Psychology, 2025)
This study investigated the interactive effects of feedback, task difficulty, and metacognitive judgment on cognitive task performance. Sixty university students (aged between 20–25 years) were randomly assigned to either a feedback or a no-feedback group. The shortened version of Raven’s Progressive Matrices (consisting of three task sets) was used to assess the cognitive task performance. Task difficulty was increased with task sets. After each set, they rated their confidence on a 4-point Likert scale. The feedback group was informed of the number of correct responses. A 2 (feedback: yes vs no) × 3 (task difficulty: low vs medium vs high) × 2 (metacognitive judgement: low vs high) three-way mixed analysis of variances revealed a significant main effect of feedback on performance: participants who received feedback consistently outperformed those who did not. A significant interaction between feedback and task difficulty, F(1, 11) = 30.994, p < .001, η² = .156, indicated that feedback was particularly effective under high-difficulty conditions. However, none of the other main effects and interaction effects was found to be significant. The results emphasize the importance of feedback under high cognitive load. Future research should examine how individual differences and feedback types shape learning and strategy use. Bangladesh Journal of Psychology, Vol. 25, December 2025, pp. 68-79